calcule
a)P(X)=2X^4-3X^2+X-1 para X=2
b) P(x)=-x^3+4x-2x para x=-1
Soluções para a tarefa
Respondido por
0
a) p(x) = 2x⁴-3x²+x-1
p(2)= 2. 2⁴-3.2²+2-1
p(2)= 2.16-3.4+2-1
p(2)= 32 -12 +2 -1
p(2)= 20+2-1
p(2)= 21
b)p(x)=-x³+4x-2x
p(-1)= - (-1)³+4.(-1)-2.(-1)
p(-1)= - (-1) -4+2
p(-1)= +1-4+2
p(-1)= - 1
p(2)= 2. 2⁴-3.2²+2-1
p(2)= 2.16-3.4+2-1
p(2)= 32 -12 +2 -1
p(2)= 20+2-1
p(2)= 21
b)p(x)=-x³+4x-2x
p(-1)= - (-1)³+4.(-1)-2.(-1)
p(-1)= - (-1) -4+2
p(-1)= +1-4+2
p(-1)= - 1
Perguntas interessantes
Artes,
10 meses atrás
Matemática,
10 meses atrás
História,
10 meses atrás
Matemática,
1 ano atrás
Pedagogia,
1 ano atrás
Química,
1 ano atrás
História,
1 ano atrás
Português,
1 ano atrás